2012
DOI: 10.1002/ajim.22112
|View full text |Cite
|
Sign up to set email alerts
|

Excess healthcare costs associated with prior workers' compensation activity

Abstract: The results reveal that individuals with prior WC claims had higher probability of filing a group health medical claim and higher average monthly medical costs in all sectors. This suggests that a part of employer liability costs related to WC gets shifted to the group health medical insurance system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
(33 reference statements)
2
6
1
Order By: Relevance
“…We used the same large-employer database as Bhattacharya and Park. 13 Nevertheless, our study differs from their study in at least two ways. First, their major objective was to examine excess GHI costs between workers with prior WC claims and workers without prior WC claims.…”
contrasting
confidence: 63%
See 1 more Smart Citation
“…We used the same large-employer database as Bhattacharya and Park. 13 Nevertheless, our study differs from their study in at least two ways. First, their major objective was to examine excess GHI costs between workers with prior WC claims and workers without prior WC claims.…”
contrasting
confidence: 63%
“…Medical costs not covered by WC were estimated at $14.22 billion covered by other insurance, $7.16 billion covered by Medicare, and $5.47 billion covered by Medicaid. In a study using a database of 16 large employers, Bhattacharya and Park 13 reported that workers with a history of prior WC claims were more likely to file group health medical claims and had higher average monthly medical costs over a 3-year period. In summary, it seems that non-WC insurance systems at least partially cover work-related injury and illness costs.…”
mentioning
confidence: 99%
“…Our results were qualitatively similar to the results from Afsaw, Rosa, and Mao (20) but our odds ratios and estimated expenditures were higher than the results from Bhattacharya and Park, although they looked only at one month post-injury rather than three (18). We evaluated only patient care workers, a group with higher than average injury rates and presumably good access to care and were able to capture a wide array of injuries including those without worker’s compensation claims.…”
Section: Discussionsupporting
confidence: 86%
“…Each showed that workers’ compensation covers well under 100 percent of these costs with estimates ranging from 46 to 56 percent of medical costs of injured construction workers paid by workers’ compensation (1618). Estimates for Hispanic construction workers, immigrant workers, and those with persistent disabilities were even lower (1719).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation